Affective Responses to Both Climbing and Nordic Walking Exercise Are Associated With Intermediate-Term Increases in Physical Activity in Patients With Anxiety and Posttraumatic Stress Disorder - A Randomized Longitudinal Controlled Clinical Pilot Trial - Bichler, Carina S.; Niedermeier, Martin; Hüfner, Katharina; Gálffy, Mátyás; Sperner-Unterweger, Barbara; Kopp, Martin (Frontiers in Psychiatry, 2022)
Background: Exercise programs have shown anxiolytic effects in psychiatric patients. Adherence to exercise programs and subsequent long-term lifestyle change is influenced by acute affective responses of the exercise programs. This research aimed to assess acute affective responses of two different exercise modalities compared to a non-exercise control program and its effects on persisting physical activity behavior change. Methods: Sixty-six out-patients diagnosed with an anxiety disorders or posttraumatic stress disorder were randomly allocated to one of three groups in a randomized longitudinal controlled clinical pilot trial: climbing (n= 26), nordic walking (n = 19), social contact control (n = 21). Affective responses were assessed pre, during, and post activity. General physical activity behavior was recorded prior to participation in the program, post program, and at follow-ups three and six months after the program. Results: Multilevel modelling analyzes of 1066 individual data points revealed increases in affective valence in the exercise sessions compared to the social contact sessions. State anxiety decreased in the climbing group compared to the social contact group. Physical activity behavior was increased immediately following the program as well as at six months follow up in both exercise groups. A larger increase in affective valence during and after the sessions was associated with higher physical activity post program. Conclusions: Climbing and conventional nordic walking exercise sessions revealed positive affective changes in out-patients indicating therapeutic potential of both modalities for acute emotion regulation. In accordance with theoretical models of human behavior change, it was judged that the experience of a more pleasant affective state following the exercise sessions induced more persisting effects on physical activity behavior after the exercise programs. Trial Registration: NCT037585998599. Available at: https://www.clinicaltrials.gov/ct2/show/NCT03758599.